The Relationship of Comorbidity with Hearing Loss in the Elderly in Nursing Homes - Eunike Arganta Malvin Sihaloho; Yuliani Mardiati Lubis; OK Yulizal (International Journal Labs, 2025)
Comorbid conditions like diabetes and hypertension can have an impact on presbycusis, which is common in the elderly. This cross-sectional study assessed 58 senior citizens (60 years of age and older) at the Binjai Elderly Social Services Unit. Blood pressure (JNC 2017 categories) and blood sugar were measured, and pure-tone audiometry was used to evaluate hearing. Blood pressure and blood sugar levels did not significantly correlate with the extent of hearing loss in either ear, according to Spearman correlation analysis (all p-values > 0.05). These results imply that the degree of age-related hearing loss in this research is not connected with blood pressure or blood sugar levels.